Drift-based seismic design procedure for Buckling Restrained Braced Frames. (April 2021) - Mousavi, Seyed Amin; Zahrai, Seyed Mehdi; Akhlagh Pasand, Ali
Highlights: A new seismic design procedure called Drift-Based Seismic Design (Dr.BSD) is introduced. Using Dr.BSD, inter-story drifts would be uniformly distributed in all stories. Using Dr.BSD, maximum inter-story drifts in all stories would remain less than their allowable values. In addition to BRBFs, other lateral load resisting systems can also be designed according to Dr.BSD. Abstract: In this paper, a drift-based seismic design (Dr.BSD) procedure is proposed by which a multi-story frame can be proportioned for a predetermined maximum inter-story drift uniformly distributed along all stories. While conceptually the proposed step-by-step design procedure is applicable for any lateral load resisting system, this study mainly focuses on Buckling-Restrained Braced Frames (BRBFs). Dr.BSD has a coupled theoretical-empirical basis developed for medium to high-rise multistory frames. It accounts for higher mode effects, flexural-shear behavior of the frame, and material and geometrical nonlinearities. From nonlinear dynamic analyses, it is shown that regular or moderately irregular BRBFs designed according to Dr.BSD would experience a rather uniform inter-story drift distribution close to the predefined target inter-story drift. In addition to the maximum inter-story drift, residual inter-story drift would be rather uniform in all stories. Sensitivity studies show that Dr.BSD is applicable for different target ductility demands, different target inter-story drifts, frames with different aspect ratios, and different design spectra with different soil types.